Clostridium butyricum B1 alleviates high‐fat diet‐induced steatohepatitis in mice via enterohepatic immunoregulation. Issue 9 (September 2017) - Zhou, Da; Pan, Qin; Liu, Xiao‐Lin; Yang, Rui‐Xu; Chen, Yuan‐Wen; Liu, Chang; Fan, Jian‐Gao
Abstract: Background and Aim: Enterohepatic immunologic derangement is associated with non‐alcoholic steatohepatitis. Here, we investigated whether Clostridium butyricum B1 (CB) would be an effective immune‐targeted substance to attenuate steatohepatitis in mice. Methods: Thirty mice were randomized into a control group fed with common forage, a high‐fat diet (HFD) group fed an HFD for 16 weeks, and an HFD + CB group treated with CB for the latter 8 weeks. Inflammation‐associated or metabolism‐associated genes in the liver or epididymal fat tissue were quantified; intrahepatic and intestinal immune factors were detected. Further short‐chain fatty acids in the cecal contents or liver were measured, and differentiations of T cells in vitro were analyzed. Results: Characteristics of non‐alcoholic steatohepatitis in the HFD group were obvious and were significantly attenuated in the HFD + CB group. The messenger RNA levels of monocyte chemotactic protein‐1 and tumor necrosis factor‐α in the liver and epididymal fat tissue were increased in the HFD group compared with the control group and were downregulated in the HFD + CB group. Intrahepatic and intestinal interferon‐γ and interleukin (IL)‐17 were significantly increased, whereas forkhead box P3, IL‐4, and IL‐22 were significantly decreased in the HFD group compared with the control group. However, these intrahepatic or intestinal immune changes were reversed after CB intervention. Furthermore, butyrate in the cecal content and liver of the HFD + CB group was significantly elevated. An in vitro investigation showed that sodium butyrate promoted CD4 + T cell differentiation into Th2, Th22, or Treg, whereas it inhibited CD4 + T cell differentiation into Th1 or Th17 under a cytokine milieu, which was mimicked by Trichostatin A. Conclusion: Clostridium butyricum B1 could attenuate HFD‐induced steatohepatitis in mice partially through butyrate‐induced enterohepatic immunoregulation.